2021
DOI: 10.1111/cogs.13029
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Models of Category Concepts Based on Names of Category Members

Abstract: Cognitive scientists have long used distributional semantic representations of categories. The predominant approach uses distributional representations of category‐denoting nouns, such as “city” for the category city. We propose a novel scheme that represents categories as prototypes over representations of names of its members, such as “Barcelona,” “Mumbai,” and “Wuhan” for the category city. This name‐based representation empirically outperforms the noun‐based representation on two experiments (modeling huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…A different question is why should categories of people be harder to decode than categories of places in classification analyses ( Figure 7 ). We do not have a full story here, but we will just point out that social concepts are an idiosyncratic type of category, falling in between abstract and concrete concepts (Anderson et al, 2014 ; Rice et al, 2018 ; Conca et al, 2021 ), and that we found, consistently with the literature (Westera et al, 2021 ), a similar pattern of results in our clustering analysis for distributional models ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A different question is why should categories of people be harder to decode than categories of places in classification analyses ( Figure 7 ). We do not have a full story here, but we will just point out that social concepts are an idiosyncratic type of category, falling in between abstract and concrete concepts (Anderson et al, 2014 ; Rice et al, 2018 ; Conca et al, 2021 ), and that we found, consistently with the literature (Westera et al, 2021 ), a similar pattern of results in our clustering analysis for distributional models ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…Performance is above chance for most models in all possible labellings, for fine-grained categorical labels as well. The toughest discrimination is the one where both individual and category vectors for people are used, and in this respect others have already found that social categories for people are not well captured by distributional models (Westera et al, 2021 ). Also, in general, performance worsens when clustering vectors for individuals and categories together, as already observed by Gupta et al ( 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mack, Love, and Preston (2018) observed that multiple episodes must be experienced in the process of concept formation. Westera, Gupta, Boleda, and Padó (2021) demonstrated that concept categories can be formed through exposure to vocabulary in a bottom-up manner, with high frequency of temporally and conceptually co-occuring words forming a stronger part of the mental network of the concept than terms less frequently associated (for further evidence, see Banks, Wingfield, & Connell, 2021; Mack et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between word representations and concepts is nuanced; seeWestera & Boleda 2019;Westera et al 2021 for discussion.…”
mentioning
confidence: 99%